Investigation on the impact of foliar application using varying quantities of chelated iron and dry yeast extract on specific physical and chemical attributes of pomegranate trees. - Zainab S. Khalaf , Zainab S. Khalaf; Mahmoud S. Abdul-Wahid, Mahmoud S. Abdul-Wahid (University of Thi-Qar Journal of agricultural research, 2024)
The investigation took place in the Al-Khamisat region, located in the southeast of Dhi Qar Governorate, during the 2023 growing season. The study focused on pomegranate trees in a private orchard. A total of twenty-seven pomegranate trees, which were uniform in terms of size and growth, were selected as experimental units to investigate the impact of applying chelated iron and dry yeast extract, as well as their interaction, on various physical and chemical attributes of Slimmi variety pomegranate trees. The experiment followed a completely randomized block design, incorporating two factors. The first factor involved spraying with chelated iron at three concentrations (0, 250, 500) mg L-1, while the second factor involved spraying with dried yeast extract at three concentrations (0, 5, 10) g L-1. Each treatment was replicated three times. There are a total of 27 experimental units, with each experimental unit represented by one tree. The outcomes were as follows: The Y3 treatment exhibited superior characteristics in terms of leaf area (2.494 cm2), stem diameter (24.46 mm), height (197.2 cm), and new growth averaging (29.78 cm). The Y3 treatment demonstrated superior chemical features in the following areas: dry matter content of 46.53 g, chlorophyll content of 51.82 mg per 100 g of fresh weight, carbohydrate content of 4.20 mg per gram of dry matter, and protein content of 10.85%. Regarding chelated iron, the F3 treatment demonstrated superior performance in the following characteristics: leaf area (2.601 cm2), stem diameter (26.74 mm), height (209.1 cm), and new growth (29.56 cm). The F3 treatment exhibited superior chemical features in terms of dry matter content (46.06 g), chlorophyll content (49.73 mg per 100 g), carbohydrate content (4.19 mg per g of dry matter), and protein content (10.91%). In regards to the binary interaction between dry yeast extract and chelated iron, the F3 Y3 treatment resulted in a plant height of 235.0 cm and new growths of 34.67 cm at a concentration of 500 mg L-1 mm. The treatment also performed exceptionally well in terms of dry weight (58.84 g), chlorophyll content (54.32 mg per 100 g), carbohydrate content (4.40 mg per gram of dry matter), and protein content (11.74%).